Desain Formulir Pendukung Surveilans Infeksi Nosokomial di Rumah Sakit Baladhika Husada Jember - Ana Nafidatul Nafidatul Khoiroh; Rinda Nurul Nurul Karimah; Ida Nurmawati (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Nosocomial infections if not reported will affect the quality of service and patient satisfaction. This happened at Baladhika Husada Hospital in Jember, namely the absence of a surveillance form for nosocomial infection. This form is important as evidence in determining accreditation standards because accreditation requires documentary proof in writing. This study aims to design an infection surveillance support form based on SNARS edition 1 of 2017. The type of research used in this study is the Research & Development study to design a support form for nosocomial infection surveillance. Data collection techniques using interview, observation, and brainstorming techniques. The subjects of this study were medical record officers, doctors, nurses, PPI, and SNARS accreditation team. This research resulted in identification of the physical aspects of the paper used is F4 paper with a weight of 70 gr and white. The anatomical aspects used on the form are the head of the form located at the top, there are instructions on the form, the font used is arial with a space of 1.15. The content aspect consists of completeness of items, sorting of items, grouping of items, abbreviations, symbols and ways of filling have been adapted to other forms and user needs. The results of this study are in the form of designs that are expected to be used for consideration in planning a form, especially infection surveillance forms. So that the hospital is easier in carrying out recording and reporting activities regarding nosocomial infection surveillance.